A Percepção da pessoa com deficiência sobre as políticas de inclusão: um estudo sobre leis e práticas na Universidade Federal do Pará – Campus Bragança. - MORAES, Ana Lídia de Oliveira (2022)
The study presented is the result of the Course Completion Work (TCC), which aimed to analyze the perceptions of people with disabilities regarding public policy legislation for people with disabilities and practices within the Federal University of Pará - Campus Bragança. The study, being of a qualitative character, was based on the regulatory documents on inclusion in Brazil, international and national historical panorama, and the perception of people with disabilities from questionnaires with semi-structured questions, these sources are made up of four people divided between students and Institution's servers. Data analysis occurred through the interpretation of the subjects' speech, theoretical support, legislation, and authorial analysis. The study indicated in its result the absence of comprehensive care for people with disabilities, with emphasis on architectural adaptations, the gap between legislation and practices, and the absence of a more complete training both from the institution's teaching staff and management, as well as from construction professionals and architecture. Besides, it was indicated that the paths through which Higher Education Institutions are, concerning the inclusion of people with disabilities, are still long and need to be consolidated in pedagogical, social, and other areas.